Health Status and Health Determinants of Older Immigrant Women in Canada: A Scoping Review - Sepali Guruge; Birpreet Birpreet; Joan A. Samuels-Dennis (Journal of Aging Research)
Increasing international migration in the context of aging populations makes a comprehensive understanding of older immigrant women’s health status and determinants of their health particularly urgent. Using Arksey and O’Malley’s framework, we conducted a scoping review to examine the available literature on the health of older immigrant women in Canada. We searched CINAHL, PsycINFO, Embase, Medline, and Cochrane databases for the period of 1990 to 2014 for Canadian-based, peer-reviewed studies on the topic. A total of 20 articles met the inclusion criteria. These articles were divided into six areas of focus: physical health; mental health; abuse; health promotion and chronic disease prevention; barriers to healthcare access and utilization; and health beliefs, behaviours, and practices. Our results show that the health of older immigrant women is affected by the interplay of various social determinants of health including the physical and social environment; economic conditions; cultural beliefs; gendered norms; and the healthcare delivery system. Our results also revealed that older immigrant women tend to have more health problems, underutilize preventive services, such as cancer screening, and experience more difficulties in accessing healthcare services.